The Bible vs. the Book of Mormon - Kramer, Joel P.; Johnson, Scott R.; Living Hope Ministries (Brigham City, Utah) (Brigham City, UT : Living Hope Ministries, 2005)
Investigates the historical validity of the Book of Mormon compared to the Bible.
DVD; full screen (4:3) NTSC; all regions.
Audio in English, Spanish, or Portuguese, with optional English subtitles.
Narrator: Cliff Gregory.
Bonus features: deleted scenes; additional intervew footage; previews of other Living Hope videos.
Keywords: Book of Mormon -- Controversial literature; Book of Mormon -- Relation to the Bible; Bible -- Historiography; Book of Mormon -- Historiography; Missions to Latter Day Saints; Video recordings for hard of hearing people; Book of Mormon -- Evidences, authority, etc; Documentary videos; DVD-Video discs